Objectifying Acupuncture Effects by Lung Function and Numeric Rating Scale in Patients Undergoing Heart Surgery. (14th March 2013) - Maimer, Anna; Remppis, Andrew; Sack, Falk-Udo; Ringes-Lichtenberg, Stefanie; Greten, Tobias; Brazkiewicz, Frank; Schröder, Sven; Goncalves, Mario; Efferth, Thomas; Greten, Henry Johannes
Abstract : Rationale . Poststernotomy pain and impaired breathing are common clinical problems in early postoperative care following heart surgery. Insufficiently treated pain increases the risk of pulmonary complications. High-dose opioids are used for pain management, but they may cause side effects such as respiratory depression. Study Design . We performed a prospective, randomized, controlled, observer-blinded, three-armed clinical trial with 100 patients. Group 1 (n = 33 ) and Group 2 (n = 34 ) received one 20 min session of standardized acupuncture treatment with two different sets of acupoints. Group 3 (n = 33 ) served as standard analgesia control without additional intervention. Results. Primary endpoint analysis revealed a statistically significant analgesic effect for both acupuncture treatments. Group 1 showed a mean percentile pain reduction (PPR) of 18% (SD 19, P < 0.001 ). Group 2 yielded a mean PPR of 71% (SD 13, P < 0.001 ). In Group 1, acupuncture resulted in a mean forced vital capacity (FVC) increase of 30 cm 3 (SD 73) without statistical significance (P = 0.303 ). In Group 2, posttreatment FVC showed a significant increase of 306 cm 3 (SD 215, P < 0.001 ). Conclusion . Acupuncture revealed specific analgesic effects after sternotomy. Objective measurement of poststernotomy pain via lung function test was possible.